Risk factors for progression to blast phase and outcome in 589 patients with myelofibrosis treated with ruxolitinib: Real‐world data. Issue 3 (20th April 2020) - Palandri, Francesca; Breccia, Massimo; Tiribelli, Mario; Bonifacio, Massimiliano; Benevolo, Giulia; Iurlo, Alessandra; Elli, Elena M.; Binotto, Gianni; Tieghi, Alessia; Polverelli, Nicola; Martino, Bruno; Abruzzese, Elisabetta; et al.
Abstract: The impact of ruxolitinib therapy on evolution to blast phase (BP) in patients with myelofibrosis (MF) is still uncertain. In 589 MF patients treated with ruxolitinib, we investigated incidence and risk factors for BP and we described outcome according to disease characteristics and treatment strategy. After a median follow‐up from ruxolitinib start of 3 years (range 0.1‐7.6), 65 (11%) patients transformed to BP during (93.8%) or after treatment. BP incidence rate was 3.7 per 100 patient‐years, comparably in primary and secondary MF (PMF/SMF) but significantly lower in intermediate‐1 risk patients (2.3 vs 5.6 per 100 patient‐years in intermediate‐2/high‐risk patients, P < .001). In PMF and SMF cohorts, previous interferon therapy seemed to correlate with a lower probability of BP (HR 0.13, P = .001 and HR 0.22, P = .02, respectively). In SMF, also platelet count <150 × 10 9 /l (HR 2.4, P = .03) and peripheral blasts ≥3% (HR 3.3, P = .004) were significantly associated with higher risk of BP. High‐risk category according to dynamic International Prognostic Score System (DIPSS) and myelofibrosis secondary to PV and ET Collaboration Prognostic Model (MYSEC‐PM predicted BP in patients with PMF and SMF, respectively. Median survival after BP was 0.2 (95% CI: 0.1‐0.3) years. Therapy for BP included hypomethylating agents (12.3%), induction chemotherapy (9.2%), allogeneic transplant (6.2%) or supportive care (72.3%). Patients treated with supportive therapy had a median survival of 6 weeks, while 73% of the few transplanted patients were alive at a median follow‐up of 2 years. Progression to BP occurs in a significant fraction of ruxolitinib‐treated patients and is associated with DIPSS and MYSEC‐PM risk in PMF and SMF, respectively.